HUSIP-HUSIP DALAM TORTOR HATA SOPISIK PADA MASYRAKAT BATAK TOBA : KAJIAN INETRAKSI SIMBOLIK - Golda S Simarmata Golda Simarmata (Gesture: Jurnal Seni Tari, 2013)
This study aims to determine how the origins Tortor Hata Sopisik, symbolic interactions contained in Husip Hata - husip in tortor tortor Sopisik and form of presentation Hata Sopisik in  Batak Toba society . The population in this study is the Toba Batak society who are in Samosir regency , artists and local traditional leader. The method used is descriptive qualitative . To complete the data in this study , researchers conducted field observations , video , interviews and documentation. The results based on the data collected can be seen that the origin of the creation of Tortor Hata Sopisik was when it was created Gondang Naposo implemented Tortor Hata Sopisik as disclosure media love for the young generation ( Naposo ) Batak Toba . Uniqueness that is characteristic of Tortor Hata Sopisik contained in Husip - husipnya . Husip - husip which means whisper , is a symbolic interaction that has meaning disclosure of his love for the opposite sex among the young generation ( Naposo ) .